Monitoring of some strength parameters in handball - Havolli, J.; Bahtiri, A.; Begu, B.; Ibrani, A.; Makolli, S. (SportMont, 2018)
Handball is a sport, which requires high physical preparation as well as technical and tactical skills. Being tough sport scrolled with multiple players, it has huge power requirements, as well as a certain level of intelligence for solving of complex situations in the game. The aim of this research was monitoring of some strength parameters. The sample of subjects consists of 14 handball players, members of Handball Club Pristina. Subjects were female, aged 20±2 years old. The measurements were made during the training sessions, in the sports gym where they train, during the 2008/09 season, initial measurement was made in the first micro cycle of preparatory period, while the final measurement was done after the end of the championship.Paired T-test were calculated for in initial and final measurement. The majority of variables have no statistically significant differences, and this should have come as a result of inadequate dosage of training loads and lack of proper training program.